Transcriptomic points of departure calculated from human intestinal cells exposed to dietary nanoparticles. (December 2022) - Xu, Ke; Mittal, Krittika; Ewald, Jessica; Rulli, Samuel; Jakubowski, Jennifer L.; George, Saji; Basu, Niladri
Abstract: Use of nanoparticles (NPs) in the food industry raises dietary health concerns. Assessing dietary NPs remains challenged due the vast number of products and the resource-intensive nature of toxicity testing. Advancements in high-throughput transcriptomics, coupled with benchmark dose (BMD) analysis are poised to modernize chemical safety assessments. The study objective was to derive transcriptomic point of departure (tPOD) values for common dietary NPs through dose-response analysis of 3′RNA-sequencing data. Two intestinal cell lines (Caco-2, HIEC-6) were exposed to 9 forms of Ag, SiO2, and TiO2, and expression of L1000 landmark genes was characterized. In Caco-2 cells, tPODmode concentrations were 0.4–0.6, 21–32, and 17–59 ppm for NPs of Ag, SiO2, and TiO2, respectively; in HIEC-6 cells, the respective tPOD values were 6–7, 7–9, and 3–13 ppm. Pathway BMDs across cases identified, for example, osteoclast and Th1/Th2 cell differentiation, and cell cycle, signaling, and senescence pathways. In all cases, the tPOD and pathway BMD values were lower than concentrations associated with cellular changes (e.g., generation of reactive oxygen species and proinflammatory cytokines, and cytotoxicity). These results demonstrate that transcriptomics dose-response analysis using in vitro models can help to increase understanding of a NP's mechanisms of action and derive quantitative information for dietary risk assessment.